2020
DOI: 10.1038/s41467-020-16604-y
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes show that earthquakes enhance permeability and release water from mountains

Abstract: Hydrogeological properties can change in response to large crustal earthquakes. In particular, permeability can increase leading to coseismic changes in groundwater level and flow. These processes, however, have not been well-characterized at regional scales because of the lack of datasets to describe water provenances before and after earthquakes. Here we use a large data set of water stable isotope ratios (n = 1150) to show that newly formed rupture systems crosscut surrounding mountain aquifers, leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 57 publications
4
37
0
Order By: Relevance
“…The study area is located on just south of the Beppu-Shimabara graben structure, lying between two major active fault systems, Hinagu and Futagawa strike-slip faults (Fig. 1d), for example, which activities generated the 2016 Mw 7.0 Kumamoto destructive earthquakes (e.g., Hosono et al 2019Hosono et al , 2020. As stated earlier, neither active volcanic activities nor typical subduction related magmatisms are recognized within and beneath the study area.…”
Section: Outline Of the Study Areamentioning
confidence: 94%
“…The study area is located on just south of the Beppu-Shimabara graben structure, lying between two major active fault systems, Hinagu and Futagawa strike-slip faults (Fig. 1d), for example, which activities generated the 2016 Mw 7.0 Kumamoto destructive earthquakes (e.g., Hosono et al 2019Hosono et al , 2020. As stated earlier, neither active volcanic activities nor typical subduction related magmatisms are recognized within and beneath the study area.…”
Section: Outline Of the Study Areamentioning
confidence: 94%
“…This is because the isotopic composition of rocks is significantly different from that of meteoric water; deep water-rock reactions would thus impart a distinct isotopic signature in the released groundwater. This prediction has been contradicted by several studies of the changes in groundwater composition after earthquakes (e.g., Claesson et al 2004Claesson et al , 2007Manga and Rowland 2009;Wang and Manga 2015;Hosono et al 2020). Detailed discussion on this topic, however, is deferred to Chap.…”
Section: Constraints From Chemical Composition Of the Excessmentioning
confidence: 98%
“…There are several studies of the changes in the isotopic composition of groundwater after the 2016 Kumamoto earthquake. Hosono et al (2020a) analyzed a comprehensive dataset for isotopic compositions of groundwater, spring water and river water in the affected region before and after the earthquake. They found that all waters changed their δD and δ 18 O compositions towards more depleted values after the earthquake (Fig.…”
Section: Japanmentioning
confidence: 99%